Application of Break Even Point as a Tool Sales Planning at Expected Profit Level at PT. Light of Anugrah Lestari - Meilan Ratuela; Stanly W Alexander; Natalia Y.T Gerungai (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to determine the application of break even point as a sales planning tool at the expected profit level at PT. The Light of Anugrah Lestari. The type of research used in this research is qualitative research with a descriptive qualitative approach. The types of data used are primary data and secondary data with data collection namely observation, interviews and documentation. The research results show that the sales of PT. Cahaya Aungrah Lestari has exceeded the break even point level and has generated profits. From these results PT. Cahaya Anugrah Lestari can carry out sales planning to achieve the desired profit level. Break even point provides calculation results regarding the margin of safety because the margin of safety calculation is the difference between targeted sales and sales at the break even point.